Biocomputing 2016 2015
DOI: 10.1142/9789814749411_0031
|View full text |Cite
|
Sign up to set email alerts
|

Prism: A Data-Driven Platform for Monitoring Mental Health

Abstract: Neuropsychiatric disorders are the leading cause of disability worldwide and there is no gold standard currently available for the measurement of mental health. This issue is exacerbated by the fact that the information physicians use to diagnose these disorders is episodic and often subjective. Current methods to monitor mental health involve the use of subjective DSM-5 guidelines, and advances in EEG and video monitoring technologies have not been widely adopted due to invasiveness and inconvenience. Wearabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…The final list was critically investigated by all authors, which led to the exclusion of 16 papers due to outcome measures that did not represent mood assessment (eg, happiness scales [29-31], Quality of Life [32], or Satisfaction With Life Scale [33], as these do not reflect abnormal depressed mood) or wearables that were not consumer based (eg, a Holter monitor [34] or multisensory clothing [35-37]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final list was critically investigated by all authors, which led to the exclusion of 16 papers due to outcome measures that did not represent mood assessment (eg, happiness scales [29-31], Quality of Life [32], or Satisfaction With Life Scale [33], as these do not reflect abnormal depressed mood) or wearables that were not consumer based (eg, a Holter monitor [34] or multisensory clothing [35-37]).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies only reported correlation strengths or did not include correlation results between the objective features and the outcome assessment [9,14,31,38]. For these studies, we contacted the corresponding author via email and acquired the relevant data in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…The size of each pie chart in Figure 2 reflects the total number of SFs across all studies, and each pie chart is divided in proportions of reported statistically significant (green) and statistically non-significant (red) correlation results. In cases of missing statistical evaluation (e.g., [33,41]) of the correlation value, we treated the directionality values as statistically non-significant, biasing the pie charts towards false negatives. A complete overview of the SFs and their correlation or prediction of mood is included in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting list, together with review papers from phase 1 were then used in a cited reference search by two authors (DAR, JEB) to produce the final list. The final list was critically investigated by all authors which led to the exclusion of 16 papers due to outcome measures that did not represent mood assessment (e.g., happiness scales [31][32][33], Quality of Life [34] , or Satisfaction With Life Scale [35]), or wearables that was not deemed consumer-based, e.g., an Holter monitor [36], or multisensory clothing [37][38][39]. Several studies did not include correlation results between the objective features and the outcome assessment (e.g., [9,14,33,40]).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation